Environmental impact of power generation - Hester, R. E.; Harrison, Roy M., 1948- (Royal Society of Chemistry, 1999)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. In today's automated world, the need for economic generation of power is of vital importance. However, the industry is commonly perceived as being responsible for pollution of the atmosphere and contamination of land and water. The wide-ranging subjects addressed in this book will contribute to the public understanding of science in this important area. Encompassing areas as diverse as current performance standards and the use of nuclear fuel, Environmental Impact of Power Generation also includes an historical overview of electricity supply. The emotive issues of air pollution and the ecological effects of overhead power lines are tackled, along with energy efficiency and conservation. This book will be essential reading for students and practitioners in environmental science and engineering.
Keywords: Energy industries -- Environmental aspects.; Electric power production -- Environmental aspects.; Environmental impact analysis.; elektronické knihy; electronic books